IJCM_340A: Eating Disorders And Its Associated Factors Among Medical Students Of A Government Medical College In Karnataka- A Cross Sectional Study - Anjali; Ranganath T S (Indian Journal of Community Medicine, 2024)
Background: Eating disorders are behavioral conditions characterized by severe and persistent disturbance in eating behaviors and associated distressing thoughts and emotions affecting physical, psychological, and social function. The high levels of stress affecting medical students predispose them to developing burnout and mental health problems, including eating disorders. Research and awareness efforts are crucial to understand and support the specific challenges faced by these students. Objective: To assess the prevalence of eating disorder and its associated factors among medical students a government medical college, Bengaluru. Methodology: A cross-sectional study was conducted among 200 students at a government medical college in Bengaluru. A stratified random sampling did from first year to fourth year medical students to select the study participants. The data was collected using a self-administered structured questionnaire, The Eating Attitudes Test (EAT-26), perceived stress scale (PSS) and Body Shape Questionnaire (BSQ-16B). We also calculated body mass index (BMI) for all the participants Results: 15% (30/200) of medical students were found to be at high risk for eating disorders. The prevalence of body shape concerns among the participants were found to be 28% (56/200). Eating disorders had statistically significant associations with female gender, severe body shape concerns and higher BMI (p value <0.05). Conclusion: Eating disorders and body shape concerns are an emerging area of concern among medical students. The implementation of stress reduction and eating disorders preventive program during medical schools may be beneficial for the future physicians.